DEVELOPING THE STUDENTS’ RESPONBILITY THROUGH NUMBERED HEAD TOGETHER MODEL IN SOCIAL SCIENCE LEARNING AT ELEMENTARY SCHOOL - Widyaningtyas, Harini; Winarni, Retno; Murwaningsih, Tri (International Journal of Indonesian Education and Teaching (IJIET), 2018)
This study is aimed at developing the application of responsibility through the implementation of Numbered Head Together model in the social science learning process. The type of this research was descriptive analysis using qualitative approach. The subjects of the study were the third-grade students and teachers of social science learning in Sukoharjo Sub-district. Data collection techniques in this study were documentation studies, observation, and interviews. The findings of the research were analyzed using interactive analysis of Miles and Huberman model and presented through descriptive narrative text. The results of the research show that: 1) the learning result of the third-grade students in social science subject is not maximal yet, 2) the students are not aware of the social science learning objectives for their future, 3) the teachers remain applying the conventional model, 4) the teacher has not implemented the social science learning process involving the students' responsibility. The characteristics of Numbered Head Together learning model are suitable to be applied in learning social science because it makes the students serious in learning, develop thinking skills, and improve social relationships among students that can be used as a means to develop the studenta’ responsibilities in the social studies learning process. DOI: https://doi.org/10.24071/ijiet.2018.020202